How Language Contributes to Stereotype Formation: Combined Effects of Label Types and Negation Use in Behavior Descriptions - Burgers, Christian; Beukeboom, Camiel J. (Journal of language and social psychology, 2020)
This article focuses on the role of language in social-stereotype formation through interpersonal communication. We conducted a between-subjects experiment (N = 423), in which participants were exposed to differential remarks about (members of) an unknown social group. Remarks varied in two linguistic devices: (a) label type, by distinguishing between generic and specific labels and (b) behavior descriptions, by contrasting negations and affirmations in descriptions of competent (e.g., not stupid vs. smart) and incompetent behaviors (e.g., not smart vs. stupid). Generic (vs. specific) labels increased perceived entitativity (“groupness” of category members), stereotype content (perceived competence) and perceived essentialism of described behaviors. Compared with affirmations, only the communication pattern with negations in descriptions of competent behaviors (e.g., not stupid) decreased perceived competence of group members, and increased perceived essentialism of incompetent behavior. Label type and negations did not interact, suggesting that these linguistic devices play a distinct, parallel role in stereotype formation.